Natural Caramelisation: A Sweet Dodol Snack Made from Ipomoea batatas (L.) Blackie. Sweet Potatoes with the Addition of Amorphophallus Oncopphyllus Blume. Tuber Flour as a Healthy Snack and Sustainable Food - Wahyuni; Erwin Junaidi Lubis (Athallah Publishing globalindo, 2026)
This study examines the natural caramelisation that occurs in purple sweet potato (Ipomoea batatas (L.) Blackie.) when combined with flour from the porang tuber (Amorphophallus oncopphyllus Blume.). The results of this study indicate that natural caramelisation during the production of dodol from purple sweet potato (Ipomoea batatas (L.) Blackie.) and formulated with porang tuber (Amorphophallus oncopphyllus Blume.) showed a significant effect according to Duncan’s test, and the means indicated the highest treatment across all tested variables, namely a soft texture, sweet taste, attractive colour with a reddish-purple hue, and a distinctive aroma reminiscent of sweet potato. In conclusion, it can be concluded that dodol made from purple sweet potato (Ipomoea batatas (L.) Blackie.) and formulated with porang tuber flour (Amorphophallus oncopphyllus Blume.) enhances diversity and offers a naturally sweet flavour. Analytical testing revealed that the treatment involving Purple Sweet Potato (Ipomoea batatas (L.) Blackie.) and Porang Tuber Flour (Amorphophallus oncopphyllus Blume.) yielded the highest values across all observed variables compared to the others.